IoT integrated antenna rotator - Chong, Jia Xin (2022)
This project deals with the design and fabrication of an IoT Integrated Antenna Rotator to upgrade an existing antenna rotator by integrating it with Internet of Things (IoT) technology. The objective of this thesis is to integrate Google Maps into web server with the antenna rotator system in order to achieve a speedy and high accuracy standalone antenna pointing system. This thesis describes the software development of the rotator system which includes the specification, system and software design, implementation and unit testing, integration and system testing, and finally the operation. NodeMCU ESP32 is implemented as the microcontroller in this SDP to control the system by using its central processor. A web server is developed in order to act as a user interface to interact with the antenna rotator system. Digital map is integrated with the system to attain IoT technology by using Google Maps API. The IoT Integrated Antenna Rotator is tested upon the integration and fabrication process. The antenna rotator is able to rotate to a desire location precisely through web server by using Google Maps API. The outcomes can result in significant cost and time savings, as well as increase the product reliability and user confidence in using IoT Integrated antenna pointing system.